Target of Rapamycin (TOR) Regulates the Expression of lncRNAs in Response to Abiotic Stresses in Cotton - Song, Yun; Li, Linxuan; Yang, Zhaoen; Zhao, Ge; Zhang, Xueyan; Wang, Lingling; Zheng, Lei; Zhuo, Fengping; Yin, Huan; Ge, Xiaoyang; Zhang, Chaojun; Yang, Zuoren; et al. (Frontiers in Genetics, 2019)
TOR (Target of Rapamycin) kinase is an evolutionarily conserved protein kinase, which integrates stress-related cues with growth and metabolic outputs. Long non-coding RNAs (lncRNAs) play a vital role in the regulation of eukaryotic genes. However, little is known about TOR function in regulating the expression of lncRNAs in plants. In this study, four putative homologous genes encoding the TOR protein were identified by utilizing the recently completed cotton genome. TOR inhibitor AZD8055 pharmacological experiments and silencing of GhTOR genes resulted in obvious cotton growth retardation, indicating the conserved role of TOR in plant growth. The expression pattern analyses in different tissues reveals that TOR may play roles in root development, and the transcript levels of TOR genes were changed under different stresses conditions. Importantly, we found TOR may be a key player to regulate the expression of long non-coding RNAs (lncRNAs). A total of 10,315 lncRNAs were discovered in cotton seedlings, 90.7% of which were long intergenic ncRNAs. Moreover, we identified the differentially expressed lncRNAs, of which 296 were significantly up-regulated and 105 were down-regulated in TOR inactivated plants. GO and KEGG analyses of differentially expressed lncRNAs neighboring genes reveals that these differentially expressed lncRNAs targeted genes are involved in many life processes including stress response, glutathione and ribosome in cotton. A series of differentially expressed lncRNAs potentially involved in plant stress response were identified under TOR inhibition. Collectively, these results suggest that cotton TOR proteins may directly modulate the expression of putative stress-related lncRNAs and eventually play a potential role in the cotton stress response.